(The Effect Of Thermal Oxidation Time And Frying Oils To Trans Fatty Accid Forming and quality of Frying Oils) - -, Yuniarti; Hudiyono PWS, Sumi; -, Budiawan (Warta Industri Hasil Pertanian, 2009)
Trans fatty acid from commercial frying oils (coconut oil,palm oil, soybean oil and corn oil) were identified to study the effect of thermal oxidation to trans fatty acid forming.Parameters of oil quality analysis were iod number, free fatty acid, peroxide number, percentage of conugated dienae and conjugated triene, and Thiobarbituric Acid (TBA) value. The analysis of trans fatty acid and composition of oils used gas chromatography with 75 m capillary colomn from Supelco SP-2560. Standardized methodologies used for fatty acid methyl ester, quantification of trans fatty acid and oil quality analysis. Heating treatmenr for thermal oxidation was done from initial temperature 180 C in 0 minute and heating time continued until 30, 60, 90 and 120 minute. Trans fatty acid was identified as C18:2:9c, 12t isomer from palm oil, soybean oil and corn oil.These trans featty acid were presented at 0,02-0,325 before heating process and o,04-9,85 after heating process.Trans fatty acid were formed from their natural cis-isomer as result of the high temperature used. Fatty acid composition of frying oils decreased as effect of thermal oxidation. Based on frying oils quality analysis, thermal oxidation decreased the quality of frying oils. Heating time have corellated with decrease of iod number for all of frying oils. Heating time also correlared with increase of free fatty acid, peroxide number,precentage of conugated diene and TBA value. Trans fatty acid could be from thermall oxidation. Results of oils quality analysis, thermal oxidation decreased oils quality and fatty acid composition.